The Central Nervous System as a Site of Action for the Coronary Vasoconstrictor Effect of Digoxin - Hasan Garan; Thomas W. Smith; W J Powell (1974)
Digitalis is known to have a vasoconstrictor effect in the coronary circulation. Recent studies have demonstrated that the coronary vasoconstrictor effects of acetylstrophanthidin and digoxin are neurally mediated via alpha adrenergic fibers. In the present study, experiments were done in 20 dogs anesthetized with chloralose and urethane to study the central nervous system as a possible site of action for this vasoconstrictor effect of digoxin. After the intravenous administration of 1.0 mg digoxin, cerebrospinal fluid concentrations of digoxin rose to a peak of 2.3+/-0.4 (SEM) ng/ml at 15 min, temporally corresponding to the peak in coronary vascular resistance change of +20.0+/-2.5% of control in the paced canine heart. Submicrogram digoxin injections into the lateral cerebral ventricle produced a significant increase in coronary vascular resistance, the latter injection producing a peak increase in coronary vascular resistance of 12.4+/-1.2% of control. Cross-perfusion experiments, where the isolated head of the operative dog was perfused from a donor dog receiving digoxin, thus keeping digoxin levels in the remainder of the operative dog very low, showed a similar degree of coronary vasoconstriction. Thus, the central nervous system appears to be an important site of action for the early coronary vasoconstrictor effect of digoxin.